Tomaševska problēma - Danemane, Kristīne (Latvijas Universitāte, 2010)
Maģistra darbā aplūkota Tomaševska problēma par noteikta veida vienības vektoru skaitu Eiklīda n - dimensiju telpā R. Darbā iegūts tās atrisinājums, ja n = 2, ..., 7.

Tomaszewski's problem about the number of certain type of unit vectors in n - dimensional space R has been considered in this master’s paper. The solution has been obtained for n = 2, ..., 7.
Tomaszewski`s Problem
Keywords: Matemātika